Bahasa Inggris - Supandi, Muhammad Diaz; Khoiri, Muhammad Abdan; Al Azhmi, Ishmaelasta Ghafrilla; Munawar, Ali Mahfuz; Nasution, Alhafidh (ZAD Al-Mufassirin, 2025)
The escalating global ecological crisis necessitates a new approach for a new approach to reconstruct the relationship between humans and nature. One relevant philosophical perspective is deep ecology, which emphasizes the intrinsic equality of all ecological entities and advocates for a radical transformation of the dominant anthropocentric paradigm. Although often associated with Western thought, this concept finds resonance in the discourse of Islamic ecotheology. This research aims to examine the ecological principles in the exegesis of the Qur'an through a comparative analysis of the thoughts of two prominent figures in contemporary Islamic eco-philosophy: Mutawalli al-Sya'rawi and Fazlun Khalid. This study employs a qualitative comparative analysis of the exegetical works of al-Sya'rawi and Fazlun Khalid, focusing on their interpretations of key Qur'anic verses central to ecological ethics, such as the concepts of the Trust (QS Al-Aḥzāb: 72), Balance (QS Al-Raḥmān: 7-9), and the inherent value of creation (QS Al-Anʿām: 38).The findings reveal that al-Sya'rawi developed a metaphysical and spiritual framework. Viewing nature as a divine hierophany (tajalli), while Khalid offers a pragmatic-participatory ecological ethics grounded in maqāṣid syarī'ah and the prophetic sunnah. This research contributes to the enrichment of Islamic ecological epistemology through the complementary synthesis of these two approaches and provides an integrative perspective on the role of Islam as a transformative solution to the global environmental crisis.